Content of the principle of legal certainty as an essential component of the rule of law - Kravchuk, Valentyna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article is devoted to determining the content of the principle of legal certainty as a necessary component of the rule of law. The author proves that the principle of legal certainty is a fundamental and complex element of the rule of law. The components of the principle of legal certainty are, in particular, accessibility of the law, predictability of the legislation, stability of the law, legitimate expectations, the impossibility of the reverse effect of the law, no punishment without the law, the inability to be held twice responsible for the same thing, and the finality of court decisions. The analysis of sources allows us to argue that the principle of legal certainty is exactly actualized through the need for stable legal regulation, which is revealed through the statics and dynamics of law. Static is manifested through the stability of the current legal regulation of social relations, and law enforcement acts, including judicial decisions ensure a certain elasticity, smoothness and necessary flexibility, which provide the necessary dynamics of law.